Cylindrocolea rhizantha (Cephaloziellaceae, Marchantiophyta)—a new record for Asia from the Western Ghats, India - Williams, Z.h.; Daniels, A.e.d.; Gradstein, S.r. (Phytotaxa, 2025)
The liverwort Cylindrocolea rhizantha, so far known only from the American continent, has been discovered in the Sirumalai Hills of the Western Ghats, Tamil Nadu, India. It constitutes the first report of the species from India and Asia. A detailed description along with a photographic plate, a distribution map and a key to the species of genus Cylindrocolea recorded from India are provided.